2013
DOI: 10.1245/s10434-013-2926-5
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Nutritional Index Predicts Long-term Outcomes of Gastric Cancer Patients Independent of Tumor Stage

Abstract: The PNI is a simple and useful marker for predicting the long-term outcomes of gastric cancer patients independent of the tumor stage. Based on our results, we suggest that the PNI should be included in the routine assessment of gastric cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
227
2
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 290 publications
(255 citation statements)
references
References 28 publications
10
227
2
16
Order By: Relevance
“…However, some studies have found that postoperative complications do not always have a negative impact on prognosis 40, 41, 42. Migita et al .…”
Section: Resultsmentioning
confidence: 99%
“…However, some studies have found that postoperative complications do not always have a negative impact on prognosis 40, 41, 42. Migita et al .…”
Section: Resultsmentioning
confidence: 99%
“…En el cáncer gástrico, el conocimiento de los riesgos de la cirugía y sus posibles complicaciones así como la identificación de los casos con mayores probabilidades de presentarlas son muy importantes para el paciente y para el cirujano en el proceso de toma de decisiones terapéuticas 25 . En la literatura asiática, se ha propuesto al IO como un parámetro que pudiera predecir pre-operatoriamente la frecuencia de presentación de complicaciones [5][6][7][8][9][10][11][12][13] . El IO es el producto de los valores de la albuminemia y de los linfocitos circulantes en sangre periférica.…”
Section: Resultsunclassified
“…Por todo ello, el IO se ha considerado como un marcador del estado nutricional y de la respuesta inmune del organismo frente al tumor 8,10 . El punto de corte para considerar patológico o no el valor del IO en el estudio de las complicaciones post-cirugía del carcinoma gástrico sigue en discusión 9 , oscilando entre 40 y 49 en los diferentes trabajos 5,[8][9][10][11]28 . Al igual que otros autores 29,30 , hemos empleado como punto de corte el valor de la mediana de nuestra serie.…”
Section: Resultsunclassified
See 2 more Smart Citations